A multiscale description of bond formation in cold roll bonding considering periodic cracking of thin surface films. (October 2019) - Khaledi, Kavan; Brepols, Tim; Reese, Stefanie
Highlights: A multiscale finite element framework is proposed to describe the bond formation in rolling processes. A numerical model is developed to simulate the periodic cracking of thin brittle surface films attached to ductile substrates. The present microscale model takes into account the most important mechanisms of bonding taking place along the joint interface. It is shown that the threshold surface expansion for the bond formation is dependent on the thickness and the mechanical properties of microscopic surface films. Abstract: The bond strength evolution in a roll bonding process is commonly described by means of the so-called "film theory" which explains the most important mechanisms associated with the joining by plastic deformation. Inspired by this theory, a multiscale finite element model is presented in this paper with the aim to describe the bond formation between similar metals in a cold roll bonding process. To achieve this goal, the joining of metal sheets in a rolling process is modeled by considering three different geometrical scales. First, a macroscale finite element model is developed to assess the distribution of stresses and strains along the joint interface in a rolling process. Then, a mesoscale finite element model for the joint interface is presented. The mesoscale model accounts for the periodic cracking of thin brittle surface films existing on the top of the metallic layers. This model is also used to determine a proper size for the microscale unit cell model of bonding. Finally, the focus lies on a microscale finite element model which describes the most important micromechanisms taking place during cold welding. This model is then employed to evaluate the bond strength value between the rolled metallic layers. It is shown that the model is able to provide a good description for the bond strength evolution. In addition, the effects of influencing factors on the bonding, such as the degree of plastic deformation, the thickness and the material properties of surface films are numerically investigated.